Personality, Individual Differences and Intelligence / Second Edition - Day Liz; Macaskill Ann; Maltby John (Prentice Hall, 2010)
This book provides a modern, international coverage of the key issues in individual differences research. Preface, Acknowledgements, Personality, Personality Theory in Context, Developments of Freudian Theorizing, Cognitive Personality Theories, Humanistic Personality Theories, The Trait Approach to Personality, Biological Basis of Personality I: Genetic Heritability of Personality and Biological and Physiological Models of Personality, Biological Basis of Personality II: Evolutionary Psychology and Animal Studies of Personality, Intelligence, Theories and Measurement of Intelligence, Heritability and Socially Defined Race Differences in Intelligence, The Application of Personality and Intelligence in Education and the Workplace: The Introduction of Other Intelligences, Further Debates and Applications in Individual Differences, Optimism, Irrational Beliefs, Interpersonal Relationships, Social Attitudes, An Introduction to Psychometric Testing, Glossary, References, Index.